Characterizations of dissimilar friction welding of ST37 and CK60 steels. Issue 9 (August 2016) - Azizieh, M.; Khamisi, M.; Lee, D.; Yoon, E.; Kim, H.
Abstract The aim of the current work is to study the effect of friction welding parameters such as joint design and rotational speed on the microstructure and mechanical properties of ST37 steel to CK60 steel joints. The tensile strength of the joints was determined using notch tensile tests. The hardness was measured across and perpendicular to the interface. Weld toughness was measured using Charpy impact tests. The results of notch tensile tests indicate that the strength of the weld zone is between those of the two components. The toughness of the weld zone was lower than both base materials. The fracture surface showed cleavage features. The round head samples had better results than for the flat ones.